Structural regulation chemistry of lithium ion solvation for lithium batteries - Zhongsheng Wang; Huaping Wang; Shihan Qi; Daxiong Wu; Junda Huang; Xiu Li; Caiyun Wang; Jianmin Ma (EcoMat, 2022)
Abstract The performance of Li batteries is influenced by the Li+ solvation structure, which can be precisely adjusted by the components of the electrolytes. In this review, we overview the strategies for optimizing electrolyte solvation structures from three different perspectives, including anion regulation, binding energy regulation, and additive regulation. These strategies can optimize the composition of the electrode‐electrolyte interface, enhance the anti‐oxidative stability of electrolytes as well as regulate the behaviors of anions, solvents, and Li+ during the cycling process. Moreover, we also provide our insights into these aspects as well as present perspectives on high‐performance Li batteries.